Representações sociais dos usuários do Sistema Único de Saúde sobre sua participação em Unidades de Saúde da Família do município de Ponta Grossa - PR. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Aiming at analyzing the users’ of the Unified Health System social representations about their participation in Family Health Units of Ponta Grossa municipality - PR, this dissertation seeks knowledge about their participation and is based on the Theory of Social Representations. This qualitative study, of an interdisciplinary nature, was developed using descriptive research with an exploratory structure, which had as its methodological path the bibliographic and documental research, followed by field research with the application of an online questionnaire and an interview. The study universe was the municipality of Ponta Grossa - PR and the sample was composed of 8 Family Health Units. The subjects participating in this study totaled 24 users, with 3 individuals for each selected unit. The choice of units was based on the observation of the city map, in which one unit was chosen per geographic region, and the criterion for the choice of subjects was mainly the time of unit use. The content analysis technique was used to treat the data, and the results sought to identify the representations of users in relation to their participation. This dissertation is divided into three chapters. The first one discusses the conceptual aspects of popular participation in health, its origin, the main considerations on the theme, and presents the initiatives for the consolidation of the users’ participation. This chapter discusses the importance of Primary Health Care and the Family Health Strategy, as well as the possibilities of acting through institutionalized participation channels. The second chapter discusses about the popular participation in health in Ponta Grossa municipality -PR, points out the main channels available to the population and exposes the results of the questionnaire applied in the Family Health Units. The third chapter presents the results of the field research referring to the interviews with the subjects, emphasizing the users' social representations about their participation. This study concluded that popular participation is linked to individual and collective conditions, in a universe of factors that impose values and feelings on people, which can influence decision making regarding participatory action.
Keywords: Participação Popular; Estratégia Saúde da Família; Representações Sociais; Popular Participation; Family Health Strategy; Social Representations; CNPQ::CIENCIAS SOCIAIS APLICADAS